Teenage Premarital Sexual Activity and The Role of Parents in Minangkabau - Susanti, Dewi; Erwani, Erwani; Ponda, Aprizal (Jurnal Kesehatan - STIKes Prima Nusantara, 2023)
Background: Premarital sexual behavior (PSP) among adolescents is increasingly binding, and this has an impact on their future. One of the biggest impacts is on adolescent reproductive health. Data shows that every year there is an increase in teenage pregnancies, early marriages, abortions and sexually transmitted diseases. Parents are the first and foremost caregivers for adolescents, and are a strategic opportunity to increase their role in parentingPurpose : This study aims to determine the causes of PSP in Minangkabau adolescents and the role of parents that can be used as an intervention model.Methods: This research is an explorative qualitative research where data collection was conducted using in-depth interviews. Informants were adolescents aged 10-19 years, parents, biological mothers and Subdistrict PIK-R program holdersResults: The results of the study found that the factors causing PSP were the mass media, peers, relationships with parents and shifts in values. The components of the role of parents in preventing PSP based on the causative factors of PSP were found as educators (religious education and sexual education and pornography prevention), role models (fathers as role models, analytical skills and role models for mothers), assistants (friendly attitude towards children, good attitude control towards children), counselor (communication skills, feeling safe and comfortable), communicator (practicing an open attitude, guaranteeing confidentiality and activating rules and supervision)Conclusion: The main causes of premarital sex behavior in Minangkabau adolescents are the influence of mass media, peers, relationships with parents and shifts in values. The efforts that can be made are to strengthen the role of parents as educators, parents as role models, parents as companions, parents as counselors and comunicator.